Single-Stage Revision of an Infected Total Hip Replacement Using Antibiotic-Impregnated Bioabsorbable Beads in a Canine Patient - Guthrie, James W.; Fitzpatrick, Noel (VCOT Open, 2019)
This report describes a technique and the outcome following surgical revision of a periprosthetic infected total hip replacement (THR) in a single-stage procedure with the use of antibiotic-impregnated bioabsorbable beads. A 6-year-old German Shepherd dog underwent THR 16 months previously, which subsequently became infected. The contaminated femoral and acetabular prostheses were explanted. A femoral window was used to remove the stem and cement. The endosteal surfaces of the femur and acetabulum were reamed to remove periprosthetic tissues. The femoral window was replaced and secured in position with multiple cerclage wires. A 3.5-mm locking plate was applied to the lateral aspect of the femur to prevent fracture of the proximal femoral metaphysis and trochanter. Bioabsorbable beads of calcium sulphate, impregnated with vancomycin and gentamicin, were impacted into the femoral canal followed by an uncemented femoral stem. An uncemented acetabular implant was impacted and additional antibiotic beads placed in the vicinity prior to closure. There has been no evidence of reinfection 5 years postoperatively. Analgesic and antibacterial drugs were not required during this follow-up period; activity is unrestricted with neither lameness nor pain present. Simultaneous revision of both femoral and acetabular periprosthetic infected THR implants was successfully achieved in this patient via a single-stage procedure using uncemented implants and antibiotic-impregnated bioabsorbable beads.
Keywords: infection; total hip replacement; bioabsorbable beads